Voice assessment and intervention in patients with Sexually Transmitted Diseases: a systematic review - Romero Arias, Tatiana; Castillejo Martínez, Paula; Sabater Gálvez, Lucía; Pérez del Olmo, Adrián (Revista de Investigación en Logopedia, 2024)
Sexually Transmitted Diseases (STD) are a group of highly infectious and contagious clinical conditions, with the oral cavity being the place where the first clinical manifestations appear. Moreover, in 90% of cases, the larynx is involved, which also causes alterations in the voice. Therefore, the aim of this article is to carry out a systematic review in order to highlight the voice alterations manifested by patients with STD by answering the following questions: What methods are most commonly used to assess the voice in patients with different STD? Which STD most frequently affects the voice? What type of medical treatment do patients with STDs receive? What intervention do patients with STDs require in terms of speech therapy? Nine articles were selected from Pubmed, WoS and Scopus databases. Overall, the results show that Human Papilloma Virus (HPV) is the most common STD causing voice disorders. Although most studies use only instrumental examinations, acoustic analysis, and voice scales (VHI-30 and GRBAS) are among the most commonly reported methods for voice assessment. It is striking that all patients receive medical treatment, while speech therapy has a comparatively low percentage.
Keywords: Sexually Transmitted Diseases; Speech therapy; Voice analysis; Voice pathology